2019
DOI: 10.5897/ijgmb2019.0181
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence between (TOHO-type and BES-type) extended-spectrum -lactamase genes of identified enterobacteria at Saint Camille Hospital, Ouagadougou, West Africa

Abstract: Coexistence between the TOHO-type and Brazilian extended-spectrum (BES)-type of extendedspectrum β-lactamase (ESBL)-produced by bacteria caused public health issue. Several studies have been reported on the coexistence between blaTEM, blaCTX-M and blaSHV genes in ESBL in broad spectrum enterobacteria. The present study involved the prevalence of coexistence of blaTOHO and blaBES genes in enterobacteria identified in hospitalized and outpatients at Saint Camille Hospital in Ouagadougou (Burkina Faso). Firstly, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
0
0
Order By: Relevance
“…In Africa, IMP enzymes had been in Egypt (Masoud et al, 2021;Benmahmod et al, 2019;Abbas et al, 2019), Morocco (Barguigua et al, 2013), Tunisia (Chouchani et al, 2011;Dziri et al, 2020), Tanzania (Mushi et al, 2014) and Sudan (Adam and Elhag, 2018). In Burkina Faso, most of the studies were much focused on ESBLproducing Enterobacteriaceae which occurs resistant to beta-lactam (Metuor Dabire et al, 2013;Metuor et al, 2019a;Metuor Dabire et al, 2019b;Tiemtore et al, 2022) at the expense of carbapenemases, mainly MBL despite the threat they represent for heath care. Nevertheless, previous studies (Sanou et al, 2020;Dembele et al, 2021;Kabore et al, 2022Kabore et al, , 2023 have reported resistance to carbapenems in GNB by the production of carbapenemases.…”
Section: Introductionmentioning
confidence: 99%
“…In Africa, IMP enzymes had been in Egypt (Masoud et al, 2021;Benmahmod et al, 2019;Abbas et al, 2019), Morocco (Barguigua et al, 2013), Tunisia (Chouchani et al, 2011;Dziri et al, 2020), Tanzania (Mushi et al, 2014) and Sudan (Adam and Elhag, 2018). In Burkina Faso, most of the studies were much focused on ESBLproducing Enterobacteriaceae which occurs resistant to beta-lactam (Metuor Dabire et al, 2013;Metuor et al, 2019a;Metuor Dabire et al, 2019b;Tiemtore et al, 2022) at the expense of carbapenemases, mainly MBL despite the threat they represent for heath care. Nevertheless, previous studies (Sanou et al, 2020;Dembele et al, 2021;Kabore et al, 2022Kabore et al, , 2023 have reported resistance to carbapenems in GNB by the production of carbapenemases.…”
Section: Introductionmentioning
confidence: 99%